Analisis Peluang Bahasa Indonesia Menjadi Bahasa Internasional dalam Perspektif Pengguna Media Sosial pada Mahasiswa UNIMED Fakultas Ekonomi - Alfath Fatiha Jihad Daulay; Yasir Almi Tanjung; Jhonson Samuel Manurung; Ahmad Hadi Ramadhan; Rosmaini Rosmaini (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to analyze the role of social media in the spread of Indonesian among students and evaluate the potential of the language to become an international language. Using a qualitative approach, data was collected through a questionnaire distributed to students at the Faculty of Economics, State University of Medan. The results of the study showed that 87.9% of respondents used social media every day, and 69.7% considered the role of social media to be very important in introducing Indonesian internationally. Although most respondents believe that Indonesian has the potential to become an international language, they identified several barriers, such as inappropriate language use and lack of support from the community and government. The recommendations put forward include active promotion of the Indonesian language on social media, improvement of the overseas education curriculum, and collaboration with international influencers.